Clinical Breast Tomosynthesis : a Case-Based Approach. - Salkowski, Lonie R. (Thieme, 2017)
Digital breast tomosynthesis (DBT), popularly called ""3D mammography"" is a state-of-the-art breast imaging technology that provides the ability to view inside the breast, layer by layer. Advantages of DBT include elimination of superimposed tissue, improved detection of otherwise hidden lesions, and significantly higher cancer detection rates compared to conventional mammography. Although it is increasingly being implemented in imaging centers, hands-on clinical learning tools have been lacking - until now. Written by renowned breast imaging specialists, this multimedia textbook is the most.